Peta Gerakan Islam Radikal Kontemporer Di Indonesia - Rijal Mumazziq Z (FALASIFA : Jurnal Studi Keislaman, 2020)
In the last two decades, the radical Islamic movement in Indonesia has flourished. Starting from solidarity with the slumped Islamic world, returning to the teachings of the Koran and hadith, rejection of Western domination of a Muslim state, to inflating the spirit of jihad, and efforts to realize an "Islamic" system through the Islamic State and the Khilafah. This action has parallel with global movements, both in the form of ideology and interconnected international networks. This article attempts to map the network for the growth of the extremist movement in Indonesia and the nature of its movement.